UPAYA MENINGKATAN HASIL BELAJAR EKONOMI MELALUI MEDIA KOMIK SAINS PADA MATERI PERTUMBUHAN DAN PERKEMBANGAN EKONOMI KELAS XI IPS SMA NEGERI 2 SIGLI TAHUN PELAJARAN 2022/2023 - Isnuddin, Isnuddin (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2023)
PTK with the title Efforts to Improve Economic Learning Outcomes through Media Science Comics on Economic Growth and Development Material for Class XI IPS SMA Negeri 2 Sigli Academic Year 2022/2023 , which aims to find out efforts to improve economic learning outcomes through the media of science comics on economic growth and development material Class XI IPS SMA Negeri 2 Sigli Academic Year 2022/2023. The subjects of this study were 18 students in class XI Social Sciences at SMA Negeri 2 Sigli for the academic year 2022/2023. To obtain the author's data using test and non-test techniques. After the data was collected, the authors processed and analyzed the data by comparing the results of observations and tests in cycle I and cycle II. The increase in the average value was 49.4 in the initial conditions to 66.7 in cycle I and to 80 in cycle II. The average value of the first cycle increased 17.3% from the initial conditions, the average value of the second cycle increased 13.3% from the first cycle. While the learning completeness in the first cycle there was an increase of 44.4% from the initial conditions, the second cycle increased 27.8% from cycle I. The overall class average score increased by 30.6%. At the end of the study there were positive changes in students regarding the understanding of economic growth and development. By using science comic media it turns out to be able to improve economics learning outcomes in the material of economic growth and development.Keywords: Learning outcomes, science comic media and economic growth and development